Gate-keeping, refugees and ethics - Kruger, Zelda (My University, 2017)
Many asylum seekers and refugees in South Africa reportedly find it difficult to access basic health care services. The issue about foreign nationals in relation to health care can be considered from different angles. The concept of access, though, points to gate-keeping. Gate-keeping is the practice that guides decision making about who has access to what and to what extent they might enjoy benefits. In this essay, the question of whether gate-keeping is a morally justifiable practice in South Africa in relation to asylum seekers and refugees’ right to basic health care services is explored. It is concluded that carefully considered and consistently implemented gate-keeping might be a morally justifiable practice that could contribute to ensuring that resources are distributed fairly. It is also argued that the kind of gate-keeping often observed is inconsistent with human rights and Ubuntu precepts. These moral frameworks seem to be the main ones shaping the view of most South Africans as well as our institutional arrangements. Considering the current South African context in which asylum seekers and refugees have difficulty in accessing basic health care services, patriotic bias claims are considered. However, it is concluded that partiality towards compatriots ought not to hold sway when any human being’s basic needs are at stake.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the Degree of Master of Arts, Applied Ethics for Professionals. Johannesburg, 2017
Keywords: Refugees--Health and hygiene--South Africa; Refugees--Medical care--South Africa; Political refugees--South Africa; Emigration and immigration--Moral and ethical aspects--South Africa